Digital Skills of School Administrators Affecting Work Motivation of Teachers Under Nongkhai Secondary Educational Service Area Office - Khantong, Nissaranan; Boobpha, Suchada (Journal of Modern Learning Development, 2021)
The purposes of this research were to : 1) To study level of school administrator’s digital skills 2) To study level of teacher’s motivation 3) To study the relationship between school administrator’s digital skills and teacher’s motivation and 4) To create a predictive equation for digital skills of school administrators affecting motivation of teachers. The sample consisted of 324 teachers in School Under The Secondary Educational Service Area Office Nongkhai. The research instrument was a 5 level-rating-scale questionnaire with the digital skills of school administrators between .557-.890 reliability at .974 and teacher’s motivation with a discriminative power between .488 - .902 and reliability at .984 The stattistical techniques employed in this analysis were frequency percentage,mean,standard deviation, Pearson product moment correlation coefficient and stepwise multiple regression analysis. The result were as follow: 1. Overall, the level of Digital skills of school administrators were found at high level. 2. Overall, the level of teachers about motivation of teachers were found at high level. 3. The relationship between digital skills of school administrators and motivation of teachers were related. 4. The analysis of the multiple regression and creating predictive equation of digital skills of school administrators affecting motivation of teachers, the 4 best predictive parameters were digital skills of enhancing the potential of organization, Searching skills practical skills and creating innovation skills at the .01 level of significance. The predicting power was 76.70 Predictive equation of raw scores: = .637 + .246(X5) + .245(X3) +.213(X4) + .142(X2) Equation of standard score: = .294(X5) +.279(X3) + .235(X4) +.160(X2)